2018
DOI: 10.7554/elife.34613
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling reveals extraordinary diversity among skeletal muscle tissues

Abstract: Skeletal muscle comprises a family of diverse tissues with highly specialized functions. Many acquired diseases, including HIV and COPD, affect specific muscles while sparing others. Even monogenic muscular dystrophies selectively affect certain muscle groups. These observations suggest that factors intrinsic to muscle tissues influence their resistance to disease. Nevertheless, most studies have not addressed transcriptional diversity among skeletal muscles. Here we use RNAseq to profile mRNA expression in sk… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
120
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(130 citation statements)
references
References 65 publications
9
120
0
1
Order By: Relevance
“…S4A " type="url"/> ). Recent RNAseq analysis demonstrates these skeletal muscles differ in terms of gene expression, including genes related to contractile capability ( Terry et al, 2018 ). Despite these differences, when Col1a2 , Col3a1 , Col6a2 , Col11a1 , Hdac4 and Loxl2 expression was examined, similar trends were observed across all three muscles when comparing the 6- and 8-week time points with 4 weeks ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S4A " type="url"/> ). Recent RNAseq analysis demonstrates these skeletal muscles differ in terms of gene expression, including genes related to contractile capability ( Terry et al, 2018 ). Despite these differences, when Col1a2 , Col3a1 , Col6a2 , Col11a1 , Hdac4 and Loxl2 expression was examined, similar trends were observed across all three muscles when comparing the 6- and 8-week time points with 4 weeks ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Seminal work on the muscle cell secretory transcriptome and proteome was published in 2012 by Le Bihan et al and Terry et al [89,90] Three main pathways of protein secretion by muscle cells could be identified, namely (1) conventional secretion, (2) secretion via nanovesicles with typical exosomal features, and (3) larger microvesicles (up to 200 nm in size) with distinct protein and mRNA cargo [89] ( Figure 2C). The lists of muscle-related transcripts and secreted proteins comprised 149 proteins of unassigned functions as putative interactors with other tissues and 123 transcripts that corresponded to putative myokines including BMPs, chemokines, cytokines, growth/differentiation factors (GDFs), and members of the tumor necrosis factor (TNF) family of secreted proteins and ligands for Wnt signaling (Supplemental File 10 in [90]). A third report of great interest compared the immediate effects of exercise on transcription after a first bout of exercise with the effects of a similar bout after weeks of intermittent exercise where a new level of homeostasis has already been reached (Table 1).…”
Section: Muscle Secretory Products With Endocrine Functionsmentioning
confidence: 95%
“…However, more genes were enriched in SkM only than were enriched in both SkM and heart, consistent with their differences in contractile function, developmental origin, and specific transcription factors (TFs). There is some heterogeneity in transcriptional profiles between different types of SkM [5] but differences in gene expression between SkM and non-SkM tissues are much greater [1, 5, 6].…”
Section: Introductionmentioning
confidence: 99%